2023
DOI: 10.1002/ajpa.24684
|View full text |Cite
|
Sign up to set email alerts
|

African apes and the evolutionary history of orthogrady and bipedalism

Abstract: Since the first discovery of human fossils in the mid-19th century, two subjects-our phylogenetic relationship to living and fossil apes and the ancestral locomotor behaviors preceding bipedalism-have driven the majority of discourse in the study of human origins. With few fossils and thus limited comparative evidence available to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 317 publications
0
6
0
Order By: Relevance
“…Although the African apes share very similar locomotion at least in terrestrial walking as indicated by a walking kinematic study by Finestone et al (2018), considering the different ecologies, body sizes, and millions of years of independent evolution of these species it is not surprising that research has also found differences between them both in the knuckle-walking and the positional behaviors (e.g., Williams et al, 2023). For example, the species have been shown to have ontogenetic and postural differences in their knuckle-walking behaviors (Inouye, 1994).…”
Section: Segmental Differences and Locomotionmentioning
confidence: 99%
“…Although the African apes share very similar locomotion at least in terrestrial walking as indicated by a walking kinematic study by Finestone et al (2018), considering the different ecologies, body sizes, and millions of years of independent evolution of these species it is not surprising that research has also found differences between them both in the knuckle-walking and the positional behaviors (e.g., Williams et al, 2023). For example, the species have been shown to have ontogenetic and postural differences in their knuckle-walking behaviors (Inouye, 1994).…”
Section: Segmental Differences and Locomotionmentioning
confidence: 99%
“…The purpose of this study is to explore the morphological and morpho‐structural integration within the femur‐pelvis module and their relation to the positional repertoire (i.e., posture and locomotion) in primates. To do so, we use three models of primates that exhibit distinct positional repertoires (Table 1): (1) humans ( Homo sapiens ) of which the positional repertoire is almost restricted to bipedalism with a fully orthograde posture in adults (but see Venkataraman et al, 2013); (2) olive baboons ( Papio anubis ) considered as mainly terrestrial and quadrupedal with a pronograde posture in adults (Druelle, Aerts, & Berillon, 2017; Hunt, 2016; Rose, 1977); (3) chimpanzees ( Pan troglodytes ) and bonobos ( P. paniscus ) that exhibit a wider positional repertoire (i.e., more diversity) than humans and baboons, including knuckle walking, arboreal climbing and suspensory behaviors, and both orthograde and pronograde posture (Doran, 1992; Hunt, 1992; Williams et al, 2023). For each three models, we explore potential patterns of integration at three levels: the magnitude of morphological integration between the external morphology of the pelvis and that of the femur.…”
Section: Introductionmentioning
confidence: 99%
“…Primates exhibit an important intertaxic locomotor diversity, which is reflected not only in the variable anatomy of their limbs but also in some particularities in the rest of their skeleton (Almécija et al, 2021; Fleagle, 2013; Williams et al, 2023). Given that the ribcage and the lumbar spine are the nexus between the shoulder and pelvic girdles, their configuration is highly related to the mode of locomotion in this group (Fleagle & Lieberman, 2021).…”
Section: Introductionmentioning
confidence: 99%